Private companies: The missing link on the path to net zero - Alperen A. Gözlügöl; Wolf-Georg Ringe (Leibniz Institute for Financial Research SAFE, 2022)
Global consensus is growing on the contribution that corporations and finance must make towards the net-zero transition in line with the Paris Agreement goals. However, most efforts in legislative instruments as well as shareholder or stakeholder initiatives have ultimately focused on public companies: for example, most disclosure obligations result from the given company's status of being listed on a stock exchange. This article argues that such a focus falls short of providing a comprehensive approach to the problem of climate change. In doing so, it examines the contribution of private companies to climate change, the relevance of climate risks for them, as well as the phenomenon of brown-spinning. We show that one cannot afford to ignore private companies in the net-zero transition and climate change adaptation. Yet, private companies lack several disciplining mechanisms available to public companies such as institutional investor engagement, certain corporate governance arrangements, and transparency through regular disclosure obligations. At this stage, only some generic regulatory instruments such as carbon pricing and environmental regulation apply to them. The article closes with a discussion of the main policy implications. Primarily, we propose extending sustainability disclosure requirements to private companies. Sustainability disclosures aim at promoting a transition to a greener economy, rather than (only) protecting investors by addressing information asymmetry. Therefore, these disclosures should encompass private companies that are of relevance for the net-zero transition. Such disclosures can be a powerful tool in shedding light on the polluting private companies that have so far been in the dark as well as serving as a disciplining mechanism.
Keywords: G38; K22; 330; private companies; net zero transition; sustainability disclosures; brown-spinning; climate change; private equity